Insertion of disciplines on information literacy in the Brazilian Library Science courses - Mata, Marta Leandro da; Silva Casarin, Helen de Castro [UNESP] (Univ Federal Santa Catarina, 2018)
The librarian is considered one of the main responsible person for disseminating to educational institutions and their professional staff the proposal of information literacy, in order to promote it as an integral part of the teaching-learning process. In this context, some questions about this professional formation should be object of reflection: does the Library Science courses have contemplated in their curricular matrices the disciplines focused specifically on information literacy? The aim of this article was to verify how information literacy courses have been approached in Library Science Undergraduate Programs in Brazil by describing their main content and emphasizing: the concepts; the different programs; the application contexts; the didactic training; the information skills; the learning resources; and, the educational librarian role. Thus, a qualitative research was conducted, performing content analysis of curricula and syllabuses of Library Science Undergraduate Programs. It was found that 10 over 39 courses in Brazil have information literacy courses, with seven of them having mandatory character and three optional; hence, greater topic coverage is provided to the students, with significant content in their course catalogs and syllabuses which contributes to qualify trainers/instructors in information literacy programs.
Keywords: Information Literacy; Librarian Science; Librarian formation; Information literacy courses